Isolation and characterization of cold sensitive pex6 mutant of the methylotrophic yeast Hansenula polymorpha - Nazarko, V. Y.; Pochapinsky, O. D.; Nazarko, T. Y.; Stasyk, O. V.; Sibirny, A. A. (Біополімери і клітина, 2002)
A cold sensitive (cs) suppressor mutant was isolated from the H. polymorpha pex6 strain defective in peroxisome biogenesis. The restored cs pex6 growth on methanol at a permissive temperature was associated with the presence of morphologically normal peroxisomes. The enlarged peroxisomes present at restrictive temperature failed to support methylotrophic growth in the cs pex6 strain. The isolated mutation has no effect on the peroxisome degradation in H. polymorpha.